Exploring mental health literacy and formal and informal help-seeking intentions among Palestinian adolescents in Israel: insights from the MHLS-Arabic-adolescents tool - Abo-Rass, Fareeda (Frontiers in Psychiatry, 2024)
BackgroundMental health literacy (MHL) is a crucial concept in mental health because it promotes positive mental health outcomes and behaviors across various demographics, including adolescents.AimsThis study utilized the MHLS-Arabic-Adolescents tool to investigate MHL among Palestinian adolescents in Israel, aiming to explore its significance in determining intentions to seek formal and informal mental health help separately.MethodsA cohort of 172 adolescents (with a mean age of 16.25 ± 1.25 years, comprising 64% females) completed assessments measuring their intention for both formal and informal help-seeking, levels of psychological distress, MHL, and various sociodemographic and clinical characteristics. This study uses the same dataset from previous research on formal help-seeking, with an expanded focus on informal help-seeking and MHL using an adapted tool.ResultsParticipants reported medium to high levels of MHL factors, demonstrating stronger intentions to seek informal help compared to formal. “Knowledge of where to seek information” and “Attitude toward mental illness” emerged as the significant MHL factors determining formal help-seeking intentions, whereas ‘attitudes toward mental illness’ was identified as the sole determinant of intentions to seek informal help.ConclusionsThis study highlights the importance of MHL factors in shaping adolescents’ intentions to seek formal and informal mental health help. It emphasizes the need to strengthen informal support networks, improve adolescents’ attitudes toward mental illness, and facilitate access to mental health information. These insights offer valuable guidance for intervention programs aimed at promoting both formal and informal help-seeking behaviors among Palestinian Arab adolescents in Israel and similar groups.